Penghambatan Produksi Aflatoksin dari Aspergillus flavus oleh Kapang dan Khamir yang Diisolasi dari Ragi Tempe - Ekawati Purwijantiningsih; Ratih Dewanti-Hariyadi; C. C. Nurwitri; Istiana (alm.) Istiana (Universitas Atma Jaya Yogyakarta, 2005)
This research was carried out to study the inhibition of aflatoxin production of Aspergillus flavus by moulds and yeasts isolated from ragi tempe. The result showed that moulds found in the ragi tempe consisted of Rhizopus oligosporus, R. oryzae, R. cohnii, Mucor rouxii, Rhizomucor pusillus, Aspergillus niger and miselia sterilia. Yeasts found in the samples were Candida sp1, Candida sp2 and Trichosporon sp. Twelve mould, and yeast isolates were chosen to determine their ability on inhibition of aflatoxin production. Aspergillus flavus alone or in association with each of these isolates were inoculated in Potato Dextrose Broth and analysed for aflatoxin production at day 10. All combinations yielded less aflatoxin than the single culture of A. flavus. All isolates tested could inhibit aflatoxin production. The highest inhibition was shown by Candida sp1 (99,96%).